Diagnosis, prevalence, and outcomes of sarcopenia in kidney transplantation recipients: A systematic review and meta‐analysis. Issue 1 (20th November 2022) - Zhang, Jin‐Zhi; Shi, Wei; Zou, Min; Zeng, Qi‐Shan; Feng, Yue; Luo, Zhen‐Yi; Gan, Hua‐Tian
Abstract: The prevalence of sarcopenia and its clinical predictors and clinical impact vary among kidney transplant recipients (KTRs), in part because of different diagnostic criteria. This study aimed to assess the reported diagnosis criteria of sarcopenia and compare them in terms of prevalence, clinical predictors, and impact of sarcopenia. The Medline, Embase, and Cochrane Library were searched for the full‐length reports published until 28 January 2022. The subgroup analysis, meta‐regression, and sensitivity analysis were performed and heterogeneity was assessed using the I 2 . A total of 681 studies were retrieved, among which only 23 studies (including 2535 subjects, 59.7% men, mean age 49.8 years) were eventually included in the final analysis. The pooled prevalence in these included studies was 26% [95% confidence interval (95% CI): 20–34%, I 2 = 93.45%], including 22% (95% CI: 14–32%, I 2 = 88.76%) in men and 27% (95% CI: 14–41%, I 2 = 90.56%) in women ( P = 0.554 between subgroups). The prevalence of sarcopenia diagnosed using low muscle mass was 34% (95% CI: 21–48%, I 2 = 95.28%), and the prevalence of using low muscle mass in combination with low muscle strength and/or low physical performance was 21% (95% CI: 15–28%, I 2 = 90.37%) ( P = 0.08 between subgroups). In meta‐regression analyses, the mean age (regression coefficient: 1.001, 95% CI: 0.991–1.011) and percentage male (regression coefficient: 0.846, 95% CI: 0.367–1.950) could not predict the effect size. Lower body mass index (odds ratio (OR): 0.57, 95% CI: 0.39–0.84, I 2 = 61.5%), female sex (OR: 0.31, 95% CI: 0.16–0.61, I 2 = 0.0%), and higher age (OR: 1.08, 95% CI: 1.05–1.10, I 2 = 10.1%) were significantly associated with a higher risk for sarcopenia in KTRs, but phase angle (OR: 0.81, 95% CI: 0.16–4.26, I 2 = 84.5%) was not associated with sarcopenia in KTRs. Sarcopenia was not associated with rejections (risk ratio (RR): 0.67, 95% CI: 0.23–1.92, I 2 = 12.1%), infections (RR: 1.03, 95% CI: 0.34–3.12, I 2 = 87.4%), delayed graft functions (RR: 0.81, 95% CI: 0.46–1.43, I 2 = 0.0%), and death (RR: 0.95, 95% CI: 0.32–2.82, I 2 = 0.0%) in KRTs. Sarcopenia was found to be very common in KRTs. However, we have not found that sarcopenia had a negative impact on clinical health after kidney transplantation. Large study cohorts and multicentre longitudinal studies in the future are urgently needed to explore the prevalence and prognosis of sarcopenia in kidney transplant patients.